Penerapan Teknologi Solar Cell Automatic Trapping untuk Mendukung Pengendalian Hama Terpadu Pada Budidaya Padi di Desa Rambipuji - Risse Entikaria Rachmanita; Saiful Anwar; Bayu Rudiyanto; Cahyaning Nur Karimah; Haning Hasbiyati; Evio Tanti Nanita (P3M Politeknik Negeri Jember, 2026)
Indonesia, as an agrarian nation, is highly dependent on rice production. In 2023, national yields declined from 54.75 to 53.98 million tons of milled dry grain (GKG), partly triggered by increasing pest pressure. A similar problem occurs in Rambipuji Village, Jember, which has 221 ha of rice fields and where approximately 50% of residents are farmers. Key pest threats include brown planthopper (Nilaparvata lugens), rats, and birds. Conventional control still predominantly relies on chemical pesticides, posing ecological and health risks and undermining long-term production sustainability. This community engagement program introduced a solar-cell automatic trapping system as an environmentally friendly, renewable-energy-based alternative for pest control. Rambipuji has strong solar energy potential, with peak solar intensity of ±1024 W/m² for about five hours per day and temperatures ranging from 26–33°C. Activities included awareness campaigns on solar energy utilization, device installation in rice fields, and training on tool operation and maintenance. Implementation results show improved farmer literacy and awareness of renewable energy, reduced dependence on chemical pesticides, and effective suppression of pest populations. This initiative enhances crop productivity, strengthens local food security, and supports village-level energy self-reliance. Therefore, this technology model is feasible to be replicated in other agricultural regions as a sustainable pest management innovation.